People With Low Back Pain Display a Different Distribution of Erector Spinae Activity During a Singular Mono-Planar Lifting Task - Sanderson, Andy; Cescon, Corrado; Heneghan, Nicola R.; Kuithan, Pauline; Martinez-Valdes, Eduardo; Rushton, Alison; Barbero, Marco; Falla, Deborah (Frontiers in Sports and Active Living, 2019)
This study aimed to investigate the variation in muscle activity and movement in the lumbar and lumbothoracic region during a singular mono-planar lifting task, and how this is altered in individuals experiencing low back pain (LBP). Muscle activity from the lumbar and lumbothoracic erector spinae of 14 control and 11 LBP participants was recorded using four 13x5 high-density surface electromyography (HDEMG) grids. Root mean squared HDEMG were used to create spatial maps of the distribution of muscle activity. Three-dimensional kinematic data were recorded focusing on the relationship between lumbar and thoracic movements. In the task, participants lifted a 5kg box from knee height to sternal height, and then returned the box to the starting position. The centre of muscle activity for LBP participants was found to be systematically more cranial throughout the task compared to the control participants (P<0.05). Participants with LBP also had lower signal entropy (P<0.05) and lower absolute root mean squared values (P<0.05). However, there were no differences between groups in kinematic variables, with no difference in contributions between lumbar and thoracic motion segments (P>0.05). These results indicate that participants with LBP utilise an altered motor control strategy to complete a singular lifting task which is not reflected in the movement strategy. While no differences were identified between groups in the motion between lumbar and thoracic motion segments, participants with LBP utilised a less homogenous, less diffuse and more cranially focussed contraction of their erector spinae to complete the lifting movement. These results may have relevance for the persistence of LBP symptoms and the development of new treatments focussing on muscle retraining in LBP.